Análisis de las ventajas y desventajas del Sistema de Gestión de la Seguridad de la Información y su influencia en la competitividad de las empresas que utilizan Cloud Computing y Big Data en el Ecuador - Coello Yagual, Ricardo Rafael (2018)
This research work reflects the analysis of the advantages and disadvantages of information security in the decision, making process of companies that use Cloud Computing and Big Data in Ecuador. To carry out the analysis, the essential variables that influence the decision-making process were identified. The study of ISO 217001 is also presented as an important element in the proposal for the implementation of the Information Security System in organizations, as a tool to protect structured and unstructured data that come from Big Data and Cloud Computing.